HACIENDA “EL MURCIÉLAGO” INCORPORATION TO SANTA ROSA NATIONAL PARK: A GEOPOLITICAL SCHEME (1978-1986) - Madriz-Sojo, Gabriel (2020)
This paper approaches the emergence of Murciélago’s area from Santa Rosa National Park not only as a protected area with remnants of the dry tropical forest (especially relevant due to its conservation of Costa Rica’s north pacific regional ecosystems), but also as a power space, conditioned by its border location with Nicaragua and Central American and international geopolitical contexts. This zone experienced several reconfigurations of social practices developed during the temporal scale of study. This reconfigurations were due to the changing elite policies: from an incipient conservationist tendency initiated by Hacienda “El Murciélago” expropriation during president Carazo Odio’s administration (19781982), to a military intensification and environmental transgression during Monge Álvarez’s administration (1982-1986), and continued but gradually diminished at the first year of Arias Sánchez’s administration (1986-1990). Through an analysis of archival, hemerographic, secondary sources, and maps, the paper develops a historical journey through the main processes of land use, territory exploitation, and distribution occurred in the mentioned space, contributing to the demystification of official speeches regarding conservation projects held by the Costa Rican State. Finally, the paper concludes that the strict implementation of binding conservationist policies inside Murcielago’s sector have been limited by a variety of political agendas in national security, a channeling of demands from various social sectors due to the economic crisis of the early 1980’s, and a marked institutional negligence in the park management.